2022
DOI: 10.1101/2022.03.08.22271980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-injury, suicidal ideation and -attempt and eating disorders in young people following the initial and second COVID-19 lockdown

Abstract: Summary Background: The initial COVID-19 lockdowns have had negative effect on different mental health measures, especially in young women. However, the impact on self-injury, suicidality and eating disorder (ED) are less elucidated and remains inconsistent. We compare self-reported self-injury, suicide ideation and -attempt and symptoms of EDs from before through different pandemic periods until spring 2021. Methods: Young participants in the Danish National Birth Cohort reported these measures in an 18-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A total of 8642 studies were screened, with 72 studies (131 samples) meeting the inclusion criteria. Among them, 16 [ 10 , 11 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], 11 [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], and 19 [ 8 , 13 , 14 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] only addressed changes in suicidal ideation, suicide attempt, and death by suicide, respectively; 25 [ 9 , 12 , 15 , 16 , 92 , 93 , 94 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 8642 studies were screened, with 72 studies (131 samples) meeting the inclusion criteria. Among them, 16 [ 10 , 11 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], 11 [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], and 19 [ 8 , 13 , 14 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] only addressed changes in suicidal ideation, suicide attempt, and death by suicide, respectively; 25 [ 9 , 12 , 15 , 16 , 92 , 93 , 94 , …”
Section: Resultsmentioning
confidence: 99%
“… Forest plot for suicidal ideation of studies [ 9 , 10 , 11 , 12 , 15 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 61 , 64 , 93 , 97 , 98 , 99 , 100 , 102 , 108 , 112 ] conducting in the non-clinical setting (Prismatic colored as red refers to the pooled estimate). …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Pre-existing self-injury and suicide ideation were binary variables de ned as being at least one time within the last year. ED symptoms were de ned as having at least monthly symptoms based on multiple variables as described in Danielsen et al [2].…”
Section: Mental Health Measuresmentioning
confidence: 99%
“…The mental health burden induced by COVID-19 pandemic and the lockdowns was suggested early on to have a disproportional impact on vulnerable subgroups, including people with a pre-existing mental health problem [1] In a previous study, we demonstrated no increase in the proportions of young people with self-injury, suicide ideation, and eating disorder symptoms (ED), respectively, following the two national lockdowns in Denmark [2]. The evidence is however inconsistent, as the impact of lockdowns on young people with pre-existing mental health problems have been suggested to be positive and negative [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%